2006
DOI: 10.1017/s0954579406060032
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of externalizing and internalizing behaviors: Factors underlying resilience in physically abused children

Abstract: Using a multisite community sample of 585 children, this study examined how protective and vulnerability factors alter trajectories of teacher-reported externalizing and internalizing behavior from kindergarten through Grade 8 for children who were and were not physically abused during the first 5 years of life. Early lifetime history of physical abuse (11.8% of sample) was determined through interviews with mothers during the prekindergarten period; mothers and children provided data on vulnerability and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
112
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(128 citation statements)
references
References 74 publications
11
112
0
5
Order By: Relevance
“…Although depression has been shown to increase from early adolescence until adulthood for girls (e.g., Galambos et al 2003), in the current study, depression slightly increased from age 12 to around age 17, followed by a decrease from age 17 to 20. This is consistent with findings showing that internalizing problem shows a curvilinear shape across adolescence (Keiley et al 2003;Lansford et al 2006). For boys, depression decreased from early to late adolescence, which is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 91%
“…Although depression has been shown to increase from early adolescence until adulthood for girls (e.g., Galambos et al 2003), in the current study, depression slightly increased from age 12 to around age 17, followed by a decrease from age 17 to 20. This is consistent with findings showing that internalizing problem shows a curvilinear shape across adolescence (Keiley et al 2003;Lansford et al 2006). For boys, depression decreased from early to late adolescence, which is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 91%
“…Black males reported higher levels of both total aggression and overt aggression than males from other racial/ethnic groups, which is consistent with a large body of literature documenting higher levels of aggressive behavior among Black males relative to White males (e.g., Lansford et al 2006). We also found that Hispanic participants reported engaging in the highest levels of reputational aggression among females, although Hispanic females did not statistically differ from other groups in post hoc analyses.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have found that different processes may be involved in the development of aggression among different racial/ethnic groups. For example, one study found that race moderated the relationship between physical discipline and adolescent externalizing problems such that physical discipline at an early age was related to subsequent increases in levels of externalizing behavior for White adolescents but to subsequent decreases for Black adolescents (Lansford et al 2006). Understanding differences in symptoms levels among racial/ethnic groups is important for targeting prevention and intervention efforts, but a better understanding of the processes by which symptoms develop is necessary for earlier targeting of high-risk individuals.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that teachers rated foster children and maltreated children not placed in foster care as having significantly more externalizing problems than the community children (the foster care and maltreated groups did not differ significantly from each other). Other studies have shown greater risk for aggression, conduct disorders, and delinquency for maltreated youth (Lansford et al, 2002;Lynch & Cicchetti, 1998; StouthamerLoeber, Loeber, Homish, & Wei, 2001) and that the negative effects of maltreatment interact with family characteristics such as parental decision making and early stress (Lansford et al, 2006). …”
mentioning
confidence: 97%